Incidence of interval cancers in faecal immunochemical test colorectal screening programmes in Italy. (March 2018) - Giorgi Rossi, Paolo; Carretta, Elisa; Mangone, Lucia; Baracco, Susanna; Serraino, Diego; Zorzi, Manuel; ,
Objective: In Italy, colorectal screening programmes using the faecal immunochemical test from ages 50 to 69 every two years have been in place since 2005. We aimed to measure the incidence of interval cancers in the two years after a negative faecal immunochemical test, and compare this with the pre-screening incidence of colorectal cancer. Methods: Using data on colorectal cancers diagnosed in Italy from 2000 to 2008 collected by cancer registries in areas with active screening programmes, we identified cases that occurred within 24 months of negative screening tests. We used the number of tests with a negative result as a denominator, grouped by age and sex. Proportional incidence was calculated for the first and second year after screening. Results: Among 579, 176 and 226, 738 persons with negative test results followed up at 12 and 24 months, respectively, we identified 100 interval cancers in the first year and 70 in the second year. The proportional incidence was 13% (95% confidence interval 10–15) and 23% (95% confidence interval 18–25), respectively. The estimate for the two-year incidence is 18%, which was slightly higher in females (22%; 95% confidence interval 17–26), and for proximal colon (22%; 95% confidence interval 16–28). Conclusion: The incidence of interval cancers in the two years after a negative faecal immunochemical test in routine population-based colorectal cancer screening was less than one-fifth of the expected incidence. This is direct evidence that the faecal immunochemical test-based screening programme protocol has high sensitivity for cancers that will become symptomatic.